Ozone oxidative preconditioning: a protection against cellular damage by free radicals - O. S. León; S. Menéndez; N. Merino; R. Castillo; S. Sam; L. Pérez; E. Cruz; V. Bocci (Mediators of Inflammation)
There is some anecdotal evidence that oxygen-ozone therapy may be beneficial in some human diseases . However so far only a few biochemical and pharmacodynamic mechanisms have been elucidated. On the basis of preliminary data we postulated that controlled ozone administration would promote an oxidative preconditioning preventing the hepatocellular damage mediated by free radicals. Six groups of rats were classified as follows: (1) negative control, using intraperitoneal sunflower oil; (2) positive control using carbon tetrachloride (CCl4) as an oxidative challenge; (3) oxygen-ozone, pretreatment via rectal insufflation (15 sessions ) and after it, CCl4; (4) oxygen, as group 3 but using oxygen only; (5) control oxygen-ozone, as group 3, but without CCl4 ; group (6) control oxygen, as group 5, but using oxygen only. We have evaluated critical biochemical parameters such as levels of transaminase , cholinesterase , super - oxide dismutase, catalase , phospholipase A, calcium dependent ATPase, reduced glutathione , glucose 6 phosphate dehydrogenase and lipid peroxidation. Interestingly, in spite of CCl4 adminis tration, group 3 did not differ from group 1, while groups 2 and 4 showed significant differences from groups 1 and 3 and displayed hepatic damage . To our knowledge these are the first experimental results showing that repeated administration of ozone in atoxic doses is able to induce an adaptation to oxidative stress thus enabling the animals to maintain hepatocellular integrity after CCl4 poisoning.